2020
DOI: 10.1007/s40618-020-01389-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled obesity status: a rarely used concept, but with particular importance in the COVID-19 pandemic and beyond

Abstract: Obesity is a chronic disease that causes and aggravates several other diseases, and early reports suggest it is an important risk factor for COVID-19 severity. Although a deeper understanding of this relationship is vital, it is also important to inform the general public about the risks and, ideally, offer strategies to mitigate the risks. As “resolution” of obesity in the short-term is not feasible, it is indeed possible that smaller weight losses and increase in physical activity can actually reduce the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…As a chronic disease, obesity cannot be reversed in the short term and many have pointed out that awareness of the relationship between obesity and COVID‐19 severity can lead to fear and panic 74–76 . However, there is evidence that modest weight loss can lead to several health benefits 96,97 . This evidence regarding reduced severity of infection is almost nonexistent, but biological plausibility exists.…”
Section: Is It Possible To Individually Reduce the Burden Of Obesity mentioning
confidence: 99%
See 3 more Smart Citations
“…As a chronic disease, obesity cannot be reversed in the short term and many have pointed out that awareness of the relationship between obesity and COVID‐19 severity can lead to fear and panic 74–76 . However, there is evidence that modest weight loss can lead to several health benefits 96,97 . This evidence regarding reduced severity of infection is almost nonexistent, but biological plausibility exists.…”
Section: Is It Possible To Individually Reduce the Burden Of Obesity mentioning
confidence: 99%
“…In a recent review, Lockhart and O'Rahilly suggest that IR is a major driver of increased risk, and if true, modest weight loss can improve it within days 7 . The concept of ‘controlled obesity’ could be a simple message as well amidst the pandemic and beyond 97 . We are aware, however, that even modest weight losses can be difficult to achieve, and the main focus is to inform that the absolute increase in risk posed by obesity can be at least partially modifiable.…”
Section: Is It Possible To Individually Reduce the Burden Of Obesity mentioning
confidence: 99%
See 2 more Smart Citations
“…"Resolution" of obesity is rarely achieved with clinical treatment. Indeed, a substantial number of studies have clearly shown that clinically achievable weight loss reduces health risks independent from the final weight (13)(14)(15). Several guidelines worldwide recommend a weight loss of 5%-10% (3,(16)(17)(18)(19), but no guideline, as far as we know, has proposed to identify and classify individuals who had lost weight in the past and were able to maintain the loss.…”
Section: Introductionmentioning
confidence: 99%